Beneath the war helmet : civil-military relations through the eyes of the Tatmadaw - Swan, Ye Tun (Nanyang Technological University, 2020)
The history of Myanmar’s civil-military relations could only be described as adversarial. Since the country achieved independence from Britain in 1948, civil war, foreign incursions, and political instability caused the Armed Forces to be the most dominant institution in the country from 1961 to 2015. Under the justification of threats to national security, the military has controlled the country for fifty-three years. Until the National League for Democracy (NLD)’s victory in the 2015 election, the country had been ruled either a military backed party or direct military rule with no meaningful opposition to their policies.